Sosialisasi Pembuatan Karya Seni Patung Dengan Teknik Butsir Untuk Membentuk Kreativitas Mahasiswa Program Studi PGMI STKIP Nurul Huda - Resti Septikasari; Ahmad Taufiq Yuliantoro; Supangat Supangat; Tri Ratna Dewi; Dyah Pravitasari (Jurnal Indonesia Mengabdi, 2021)
This Community Service is carried out on students of PGMI STKIP Nurul Huda with the aim that students have high creativity about works of art. The steps for making a sculpture using this grain technique are: The preparation stage, providing materials such as paper, scissors, glue (starch starch), water, plates, paint and items that are suitable for the statue to be made. invite students to follow what is made by the PkM team members. The completion stage is to color the shapes made by each group. The results of this socialization form various interesting shapes with colors that are no less interesting. Of course each group gets a good score. This proves that students are able to show well creativity